CURATIVE EFFECT OF ALBIZIA LEBBECK METHANOLIC EXTRACT AGAINST ADJUVANT ARTHRITIS-WITH SPECIAL REFERENCE TO BONE EROSION (International Journal of Pharmaceutical Sciences and Drug Research, 2009)
Localized bone loss in the form of bone erosions and peri-articular osteopenia constitutes important signs for the diagnosis of rheumatoid arthritis. In the present study, the effect of Albizia lebbeck Methanolic extract (AL) on the bone erosion turn over was studied by analyzing various markers of bone erosion like histological and radiological analysis of the joints in Freund’ complete adjuvant induced- arthritis in rats. The anti-arthritic activity of methanol extract of the bark of Albizia lebbeck (Mimosaceae) was evaluated against Freund’s complete adjuvant induced- arthritis induce arthritis model in rats. Arthritis was induced in rats by injecting 0.1ml of Freund’s complete adjuvant containing 6 mg of heat killed mycobacterium tuberculosis in 1ml paraffin oil into the left hind paw of the rat intradermally. AL (200 mg/kg, 400 mg/kg, 600 mg/kg body weight/day) was administered orally for 12 days. On 21st day of experiment, the histopathological and radiological observation was carried out along with rheumatoid factor and arthritic index. It can be concluded that Albizia lebbeck Methanolic extract (AL) possesses strong anti-arthritic property by modulating bone erosion.